PERAN BRAND IMAGE DALAM MEMEDIASI HUBUNGAN KUALITAS PRODUK DAN KUALITAS PELAYANAN DENGAN KEPUTUSAN PEMBELIAN - Suryantari, Ni Luh Putu Pratiwi; Respati, Ni Nyoman Rsi (E-Jurnal Manajemen, 2022)
This study aims to examine the effect of product quality on purchasing decisions, the influence of product quality on brand image, the influence of brand image on purchasing decisions, the influence of service quality on purchasing decisions, the influence of service quality on brand image, the effect of product quality on purchasing decisions through brand image as mediation, service quality with purchasing decisions through brand image as mediation. The number of samples is 150 Honda PCX motorcycle customers who live in Denpasar City. Data were collected through distributing questionnaires. The analysis technique used is path analysis. It was found that product quality has a positive and significant effect on purchasing decisions. Product quality has a positive and significant effect on brand image. Brand image has a positive and significant effect on purchasing decisions. Service quality has a positive and significant effect on purchasing decisions. Service quality has a positive and significant effect on brand image. Brand image significantly mediates the relationship between product quality on purchasing decisions and service quality on purchasing decisions. Keywords : Product Quality, Brand Image Service Quality, Purchase Decision